2016
DOI: 10.1371/journal.pone.0162113
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Gestational Diabetes on Neurodevelopment of Children in the First Two Years of Life: A Prospective Study

Abstract: ObjectiveAnalyze the relation of gestational diabetes and maternal blood glucose levels to early cognitive functions in the first two years of life.MethodsIn a prospective Singaporean birth cohort study, pregnant women were screened for gestational diabetes at 26–28 weeks gestation using a 75-g oral glucose tolerance test. Four hundred and seventy three children (n = 74 and n = 399 born to mothers with and without gestational diabetes respectively) underwent neurocognitive assessments at 6, 18, and/or 24 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 49 publications
(103 reference statements)
3
36
0
3
Order By: Relevance
“…Interestingly, these alterations in neuronal arrangement in the young adult GDM offspring were associated with impaired recognition memory, reduced anxiety level, and inattentive behavior. Therefore, offspring of GDM dams exhibit many of the cognitive changes reported in some clinical cohort studies of populations of children from mothers diagnosed with diabetes during pregnancy [36]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, these alterations in neuronal arrangement in the young adult GDM offspring were associated with impaired recognition memory, reduced anxiety level, and inattentive behavior. Therefore, offspring of GDM dams exhibit many of the cognitive changes reported in some clinical cohort studies of populations of children from mothers diagnosed with diabetes during pregnancy [36]. …”
Section: Discussionmentioning
confidence: 99%
“…The combination of human cohort studies and research using rodent models with controlled pre- and postnatal conditions has demonstrated that diabetes during pregnancy during critical stages of development affects health outcomes in the offspring [2]. Several human cohort studies have linked diabetes during pregnancy with impaired cognitive abilities [36] and psychiatric disorders [7, 8] in the offspring. Similar correlations exist between poor quality early childhood diets and cognitive performance [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Hypothyroidism can complicate the pregnancy and cause pregnancy-induced hypertension, preeclampsia, abruptio placentae, postpartum haemorrhage, impaired neurodevelopment of the infant, preterm delivery, and low birth weight [30,31]. Children born to hypothyroid mothers or to those with GDM have impaired neuropsychological development [32,33].…”
Section: Diabetes Mellitus Thyroid Dysfunction and Pregnancymentioning
confidence: 99%
“…Some studies in humans have described that maternal diabetes affects the intrauterine development of the nervous system and cognitive abilities of the offspring. While the offspring of mothers with gestational diabetes show alterations in prenatal neurodevelopment, explicit memory [11], as well as electrophysiological alterations related attention deficit [12], and motor alterations [13].…”
Section: Introductionmentioning
confidence: 99%